2012 9th International Conference on Electrical Engineering/Electronics, Computer, Telecommunications and Information Technolog 2012
DOI: 10.1109/ecticon.2012.6254160
|View full text |Cite
|
Sign up to set email alerts
|

Speaker tracking module for indoor robot navigation

Abstract: The goal of this study is to equip a mobile service robot with an ability to navigate to the human who commands the robot by speech. This paper proposes a Bayesian approach to sound source localization for speaker tracking module. Based on time delay of arrival (TDOA) features, sound source direction is classified using a naïve Bayesian network. The method requires low computational complexity and is feasible for real-time robot navigation. Based on an experiment with various parameter settings in an indoor en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…Source localization can be reactive as a modality of the interaction as presented in works that deal with following a conversation [18][19][20][21]; or it can be an essential part of the interaction, such as using sound localization to control the navigation of the robot. In particular, Teachasrisaksakul et al propose a system that follows a person through a room by her or his voice [22]. On the other hand, Li et al demonstrated a robot which plays hide and seek, using visual and audio modalities in the interaction [23].…”
Section: Previous Workmentioning
confidence: 99%
“…Source localization can be reactive as a modality of the interaction as presented in works that deal with following a conversation [18][19][20][21]; or it can be an essential part of the interaction, such as using sound localization to control the navigation of the robot. In particular, Teachasrisaksakul et al propose a system that follows a person through a room by her or his voice [22]. On the other hand, Li et al demonstrated a robot which plays hide and seek, using visual and audio modalities in the interaction [23].…”
Section: Previous Workmentioning
confidence: 99%
“…Similarly, Trifa et al [34] have presented a system that integrates sound source localization with other functionalities for moving the robot's eyes and neck towards interesting events. Teachasrisaksakul et al [31] developed an indoor robot navigation system based on sound localization. Recently, Li et al [11] demonstrated a robot that can play the game hide and seek, in which it moves according to simple voice commands given by the players and localizes the player raising his/her hand after receiving the command "localization".…”
Section: Sound Source Localization Applied In Hrimentioning
confidence: 99%